2014
DOI: 10.1038/mt.2013.291
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Therapeutic siRNA to the Lung Endothelium via Novel Lipoplex Formulation DACC

Abstract: Posttranscriptional gene silencing by RNA interference can be therapeutically exploited to inhibit pathophysiological gene expression. However, in contrast to the established effectiveness of RNAi in vitro, safe and effective delivery of siRNAs to specific organs and cell types in vivo remains the major hurdle. Here, we report the development and in vivo characterization of a novel siRNA delivery system (DACC lipoplex) suitable for modulating target gene expression specifically in the lung vasculature. Systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 33 publications
2
82
0
Order By: Relevance
“…Confocal microscopy also found that cRGD-siEGFR only aggregated around tumor tissues that had high expression of anb3 receptors, while no such aggregation was found in normal tissues or tumor tissues with low anb3 receptor expression. Compared with normal nanoparticles and liposomes, cRGD-siEGFR highly and specifically targeted tumors (Dahlman et al, 2014;Fehring et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy also found that cRGD-siEGFR only aggregated around tumor tissues that had high expression of anb3 receptors, while no such aggregation was found in normal tissues or tumor tissues with low anb3 receptor expression. Compared with normal nanoparticles and liposomes, cRGD-siEGFR highly and specifically targeted tumors (Dahlman et al, 2014;Fehring et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Fehring et al [135] characterized a novel siRNA delivery system modulating target gene expression specifically in the lung endothelium, even if they did not investigate the mechanism by which this delivery system targets specifically the lung vasculature.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Target protein expression was assessed by Western blotting of whole tissue lysates as described previously [17]. Snap frozen tissues were homogenized in a Mixer Mill and proteins were extracted in Riper-lysis buffer.…”
Section: Western Blot Analysismentioning
confidence: 99%